Dietary Shifts Among the Developmental Stages of the Ectoparasite, Argulus japonicus (Crustacea; Branchiura), Mirror Ontogeny as Shown Through Differences in Stable Isotope Ratios of Carbon (δ13C) and Nitrogen (δ15N) - Beric M. Gilbert; Milen Nachev; Bernd Sures; Annemariè Avenant‐Oldewage (Ecology and Evolution)
ABSTRACT Food web architecture and trophic interactions between organisms can be studied using ratios of naturally occurring stable isotopes of carbon (13C/12C) and nitrogen (15N/14N). Most studies, however, focused on free‐living organisms, but recently, there has been growing interest in understanding trophic interactions of parasites. The crustacean ectoparasite Argulus japonicus is a well‐studied parasite of freshwater teleost fish, which has low host specificity and a cosmopolitan distribution. Little is known about the trophic interactions between various developmental stages of this parasite and its host. This study compares stable isotope ratios of carbon (δ13C) and nitrogen (δ15N) among developmental stages of A. japonicus. It was hypothesised firstly that stable isotopes would vary among the developmental stages of the parasite with differences matching ontogenetic development of the parasite. Secondly, fractionation patterns among developmental stages would relate to different fish tissues and particles, such as algae, ingested by the parasite. Goldfish, Carassius auratus, were infected with A. japonicus, and different developmental stages of the parasite were isolated and prepared for stable isotope analysis. Differences in stable isotope enrichment correlated with the ontogenetic development of the parasite. In adult parasites, δ15N was higher than in the host's tissues, whereas stage two larvae showed the lowest δ15N values. Infection by A. japonicus alters δ13C ratios between infected and uninfected hosts, where the latter group showed lower δ13C compared to uninfected hosts. Source contribution comparison showed that algae was not incorporated into the diet of A. japonicus and tissues of the host served as the only dietary source of nourishment. These results further suggest that the diet of the parasite is mixed and correlates to the ontogenetic development of A. japonicus.